Pengaruh Metode Diskusi dan Qiro’ah dalam Pembelajaran Bahasa Arab terhadap Minat Belajar Siswa Di Kelas X MIPA MA Unggulan Amanatul Ummah Surabaya - M. Bashori (Jurnal Alfazuna : Jurnal Pembelajaran Bahasa Arab dan Kebahasaaraban, 2017)
This study aims to determine how big the influence of the method of discussion qiro'ah in learning Arabic to student learning interest in MA Unggulan Amanatul Ummah Surabaya academic year 2017-2018. Research Subject (respondent) is all students / students of class X MIPA in MA Unggulan Amanatul Ummah Surabaya academic year 2016-2017. Sampling technique in this research by using Cluster Proportional. Random Sampling technique was obtained by 52 students from population 110 students. Methods of data collection using questionnaire (questionnaire). The data analysis method used is a simple linear regression test using SPSS version 21 for windows. The research findings show that the method of qiro'ah discussion in Arabic learning has a positive and significant effect on students' interest in learning. It can be shown with the value of t count of 4.472, the regression coefficient (b) of 1.279, the significance value (p) of 0,000 (p <0.05) and the coefficient of determination (R2) of 0.310 or 31% which can be interpreted that 31% students' learning interest in learning Arabic is influenced by the method of qiro'ah discussion, while the rest of 69% is influenced by other variables not included in this research.